The Effect Financial Performance on Stock Price (Case Study of Food Company Listed on Indonesia Stock Exchange BEI) - Agustyawati, Dwi; Rais R, Muhammad (Institute for Research and Community Service, 2023)
This study aims to identify the factors that influence the stock price of food companies on the Indonesia Stock Exchange (IDX) during the 2018-2021 period, and data analysis was carried out using multiple linear regression tests using data from published financial reports of food companies and stock price data from the platform. IDX stock trading. The results of the analysis show that Earning Per Share has a significant effect on stock prices. This is because an increase in EPS can increase the potential income for shareholders, make shares more attractive, and increase the demand for these shares. In addition, Net Profit Margin also has a significant effect on stock prices because it shows higher efficiency and company profitability. This attracts investors and demonstrates the company's ability to generate significant profits. Furthermore, the Current Ratio also has a significant effect on stock prices because it can show a company's ability to pay short-term obligations easily. This gives confidence to investors that the company is able to overcome financial challenges and operate properly. However, Debt to Equity Ratio does not have a significant effect on stock prices because other factors such as company growth, industry performance, and market sentiment have a greater influence on stock prices than debt to equity ratio. Finally, the Price Earning Ratio also has no significant effect on stock prices because stock valuation is influenced by other factors such as company growth, industry conditions, and market sentiment, which are more important than the PER itself.